A Promotion Analysis of Wolof Clefts. (8th November 2012) - Torrence, Harold
<x xml:space="preserve">Abstract</x> Abstract. This article investigates the syntax of cleft clauses in Wolof. I argue that Wolof clefts are derived by the movement of the clefted constituent to the cleft position. Evidence for the movement anlaysis comes from several general and language‐specific reconstruction tests: island sensitivity, idiom chunk reconstruction, reconstruction for Principle A and Principle C, quantifier binding, negative polarity item reconstruction, and the properties of Wolof subjunctive clauses and clitics. I compare Wolof clefts to English clefts throughout and, following work going back to Schachter 1973, suggest that English clefts are also derived by overt movement of the clefted item. Using quantifier float, clausal pied piping and a wh‐copy construction, I argue that movement of the clefted item in Wolof is successive cyclic. Finally, I examine the relation between movement, Superiority, and (Strong and Weak) Crossover by comparing Wolof, English, and Yoruba.